An allelic series at the KARRIKIN INSENSITIVE 2 locus of Arabidopsis thaliana decouples ligand hydrolysis and receptor degradation from downstream signalling. (23rd July 2018) - Yao, Jiaren; Mashiguchi, Kiyoshi; Scaffidi, Adrian; Akatsu, Tomoki; Melville, Kim T.; Morita, Ryo; Morimoto, Yu; Smith, Steven M.; Seto, Yoshiya; Flematti, Gavin R.; Yamaguchi, Shinjiro; Waters, Mark T.
Summary: Karrikins are butenolide compounds present in post‐fire environments that can stimulate seed germination in many species, including Arabidopsis thaliana . Plants also produce endogenous butenolide compounds that serve as hormones, namely strigolactones (SLs). The receptor for karrikins (KARRIKIN INSENSITIVE 2; KAI2) and the receptor for SLs (DWARF14; D14) are homologous proteins that share many similarities. The mode of action of D14 as a dual enzyme receptor protein is well established, but the nature of KAI2‐dependent signalling and its function as a receptor are not fully understood. To expand our knowledge of how KAI2 operates, we screened ethyl methanesulphonate (EMS)‐mutagenized populations of A. thaliana for mutants with kai2 ‐like phenotypes and isolated 13 new kai2 alleles. Among these alleles, kai2‐10 encoded a D184N protein variant that was stable in planta . Differential scanning fluorimetry assays indicated that the KAI2 D184N protein could interact normally with bioactive ligands. We developed a KAI2‐active version of the fluorescent strigolactone analogue Yoshimulactone Green to show that KAI2 D184N exhibits normal rates of ligand hydrolysis. KAI2 D184N degraded in response to treatment with exogenous ligands, suggesting that receptor degradation is a consequence of ligand binding and hydrolysis, but is insufficient for signalling activity. Remarkably, KAI2 D184N degradation was hypersensitive to karrikins, but showed a normal response to strigolactone analogues, implying that these butenolides may interact differently with KAI2. These results demonstrate that the enzymatic and signalling functions of KAI2 can be decoupled, and provide important insights into the mechanistic events that underpin butenolide signalling in plants. Significance Statement: The receptor‐enzyme KAI2 is essential both for normal plant development and responses to karrikins in smoke, but the steps between ligand perception and early signalling events are not well established. We present the analysis of 13 new kai2 mutants and use a new fluorescent compound to show that the degradation of the receptor depends on ligand hydrolysis, but is independent of signalling.